Synthesis and Antimicrobial Activity of Some Transition Metal Complexes of o-Vanillin-L-Histidine - Sleema, B.; Ramesh Babu, M.G. (Asian Journal of Chemistry, 2010)
Complexes of Fe(Il), Co(ll), Ni(II) and Cu(II) with o-vanillin-L- histidine have been synthesised. Physical and spectral data of the chelates were determined by elemental and spectral analysis. The synthesised complexes were screened against microorganisms isolated from prawn and soil for antibacterial activity.